Innovation and market dynamics in the EPO market - Enrico Sorisio; Steinar Strøm (University of Oslo, Department of Economics, 2006)
We have estimated the demand of erythropoietin (EPO) on market data from the Nordic countries. Assuming that prices are set in a Nash-Bertrand game we determine the degree of competition in this Nordic market. We also report the impact of product innovation on welfare, e.g on consumer and producer surplus. The product innovation is the entry of Aranesp in the Nordic market. We find a positive effect related to the introduction of Aranesp in the EPO market. The high increase in consumer surplus however seems not to be accompanied by a great increase in producer surplus, whose growth is slight. Some time after the introduction of the innovation, the surplus growth does not seem to increase, it remains more or less the same (or decreases a bit). An important conclusion in our paper is that although there are few firms competing in the Nordic market for EPO, the estimated long run market power is low.
Keywords: C35; D43; I18; L11; 330; Discrete choice; demand for pharmaceuticals; monopolistic competition; EPO; Pharmazeutisches Produkt; Monopolistischer Wettbewerb; Nordeuropa; Diskrete Entscheidung